The Relationship of Psychological and Somatic Well-Being in Patients - Yauhen G. Shvaiko (Lomonosov Moscow State University, 2024)
Background. Understanding of emotional aspects of painful experiences can significantly expand the therapeutic tools for both doctors and psychologists. Objective. The focus is placed on the study of the relationship between psychological and somatic well-being of patients with pain syndrome. Study Participants. Sample included 119 people: 57 men (average age 47.9 years) and 62 women (average age 46.5 years) from the number of outpatients of the treatment and prevention institution "City Health Center #12" (Minsk). Methods. The study used: the Subjective Well-being Scale, the Numeric Pain Rating Scale (NPRS), the McGill Pain Questionnaire (MPQ), the Differential Emotion Scale, the Toronto Alexithymia Scale, and the Giessen Subjective Complaints List, GBB. Results. The analysis of the correlations of emotional state and somatic complaints has revealed similarities and specificity of subjective experiences of patients in different conditions. The correlation analysis showed a certain relationship between emotional state and well-being, which is closely related to subjective well-being. Conclusion. Subjective well-being of patients is related to psychoemotional state, health and somatic complaints, as well as, to some extent, to the level of alexithymia. Patients' well-being is related to their emotional state and negative emotions. Practical application of the results. Understanding the psychological state of the patient can be useful for developing a personalized approach to treatment and successful rehabilitation through intrapersonal resources.